OMNICHANNEL MARKETING STRATEGIES: BRIDGING THE GAP BETWEEN ONLINE AND OFFLINE CONSUMER EXPERIENCES - Wahyudin Rahman; Ansir Launtu; Muammar Revnu Ohara; Muhammad Asir; Klemens Mere (Journal of Economic, Bussines and Accounting (COSTING), 2025)
Omnichannel marketing has emerged as a critical strategy for businesses aiming to provide seamless consumer experiences across online and offline platforms. This article explores the effectiveness of omnichannel strategies in bridging the gap between digital and physical consumer interactions through a literature review of studies published since 2020. Key components such as integrated technology, personalized customer engagement, and consistent brand messaging are analyzed for their role in enhancing customer satisfaction and loyalty. The findings reveal that successful omnichannel strategies require a deep understanding of consumer behavior, robust data analytics, and alignment between online and offline operations. Practical recommendations are provided to help businesses implement effective omnichannel frameworks, emphasizing the importance of technological integration and customer-centric approaches. This study contributes to the growing body of literature by synthesizing contemporary research and offering actionable insights for improving consumer experiences in a multi-channel environment.